2018
DOI: 10.1186/s12910-018-0283-4
|View full text |Cite
|
Sign up to set email alerts
|

Community involvement in biomedical research conducted in the global health context; what can be done to make it really matter?

Abstract: BackgroundCommunity involvement in research has been advocated by researchers, communities, regulatory agencies, and funders with the aim of reinforcing subjects’ protection and improving research efficiency. Community involvement also has the potential to improve dissemination, uptake, and implementation of research findings. The fields of community based participatory research conducted with indigenous populations and of participatory action research offer a large base of experience in community involvement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…It has also given us some tools on how to navigate some of the complex issues that can arise and to apply them in our work. Many of us have even presented or written about what we have learned and applied (eg, "protecting confidentiality while disseminating locally" 15 ; "ethical tensions in GH fieldwork" 16 ; " a definition of GH for nursing" 17 ; "how can the voices of French-speaking researchers be better heard" 18 ; and "Community involvement in biomedical research in GH" 19 ).…”
Section: Training Activities Specific To Ghmentioning
confidence: 99%
“…It has also given us some tools on how to navigate some of the complex issues that can arise and to apply them in our work. Many of us have even presented or written about what we have learned and applied (eg, "protecting confidentiality while disseminating locally" 15 ; "ethical tensions in GH fieldwork" 16 ; " a definition of GH for nursing" 17 ; "how can the voices of French-speaking researchers be better heard" 18 ; and "Community involvement in biomedical research in GH" 19 ).…”
Section: Training Activities Specific To Ghmentioning
confidence: 99%
“…In addition to the potential benefits of CE, a review of evidence conducted by Attree et al highlighted the potential for unintended negative impacts (17); these include physical and mental exhaustion from the requirements of engagement that may not always outweigh the expected benefits (17). CE requires not only time and resources, but also researchers that are competent and capable of taking on the challenges of establishing this engagement with the community (18). A systematic review that analyzed community participation in health found that a community's "social hierarchies and economic or political divisions" were reflected in participation and may raise barriers influenced by power and resource prioritization [(19), p.457].…”
Section: Community Engagement In Practicementioning
confidence: 99%
“…The community engagement process continues throughout the lifecycle of a clinical trial, from concept generation through results dissemination and study close-out [ 3 , 4 ]. Community engagement is inclusive of community education, study recruitment, retention, and product adherence, and is recognized as a significant contributor to these important clinical trial elements [ 2 , 5 ].…”
Section: Introductionmentioning
confidence: 99%